2018
DOI: 10.12659/msm.909715
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Androgen Levels, Endocrine and Metabolic Indices, and Clinical Findings in Women with Polycystic Ovary Syndrome in Uygur and Han Ethnic Groups from Xinjiang Province in China

Abstract: BackgroundThe aim of this study was to compare androgen levels, endocrine and metabolic indices, and clinical findings in women with polycystic ovary syndrome (PCOS) in Uygur and Han ethnic groups from Xinjiang Province, China.Material/MethodsBetween January 2016 to May 2017 clinical data were collected from Uygur (N=82) and Han (N=100) women diagnosed with PCOS, including age, body mass index (BMI), the Ferriman-Gallwey (mFG) hirsutism score, and waist-to-hip ratio (WHR). Blood samples obtained from all study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Blood testosterone levels are considered the gold standard or reference for distinguishing female patients with PCOS from those with hyperandrogenism but not using PCOS. In various studies, the cutoff values for blood testosterone levels were reported as 2.37 nmol/L (Hahn et al, 2007) and 2.39 nmol/L (Zhao et al, 2018). These values are used to differentiate between the two conditions and aid in accurate diagnosis and treatment decisions.…”
Section: Resultsmentioning
confidence: 99%
“…Blood testosterone levels are considered the gold standard or reference for distinguishing female patients with PCOS from those with hyperandrogenism but not using PCOS. In various studies, the cutoff values for blood testosterone levels were reported as 2.37 nmol/L (Hahn et al, 2007) and 2.39 nmol/L (Zhao et al, 2018). These values are used to differentiate between the two conditions and aid in accurate diagnosis and treatment decisions.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, hirsutism was assessed through a modified Ferriman-Gallwey score (mFG) with a diagnostic level of ≥ 4-6 [9]. It is noteworthy that the expression of PCOS has varied depending on geographical and ethnic differences even in the same country [10]. Furthermore, phenotype A has been reported as dominant in more than half of published clinical data [11,12].…”
Section: Introductionmentioning
confidence: 99%